2020
DOI: 10.1101/2020.02.25.964155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DGINN, an automated and highly-flexible pipeline for the Detection of Genetic INNovations on protein-coding genes

Abstract: Adaptive evolution has shaped major biological processes. Finding the protein-coding genes and the sites that have been subjected to adaptation during evolutionary time is a major endeavor. However, very few methods fully automate the identification of positively selected genes, and widespread sources of genetic innovations as gene duplication and recombination are absent from most pipelines. Here, we developed DGINN, a highly-flexible and public pipeline to Detect Genetic INNovations and adaptive evolution in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…GBPs are present as a multigene family in vertebrates. The GBP family exhibits signs of strong evolutionary pressure with gene loss, gene duplication and neofunctionalisation (1)(2)(3) indicative of a selective adaptation to pathogens. Eleven GBPs are encoded in mice while seven GBPs are present in humans (4).…”
Section: Introductionmentioning
confidence: 99%
“…GBPs are present as a multigene family in vertebrates. The GBP family exhibits signs of strong evolutionary pressure with gene loss, gene duplication and neofunctionalisation (1)(2)(3) indicative of a selective adaptation to pathogens. Eleven GBPs are encoded in mice while seven GBPs are present in humans (4).…”
Section: Introductionmentioning
confidence: 99%
“…To perform the phylogenetic and positive selection analyses, we used the Detection of genetic innovation DGINN bioinformatic pipeline (Picard et al, 2020) that entirely automates the analyses and combines several methods to test for selection across large datasets (Figure 1A). Briefly, from each of the 334 human reference gene sequences, DGINN automatically retrieved bat and primate homologs (from NCBI nr database), curated the coding sequences, and performed a codon-alignment followed by a gene phylogenetic reconstruction (Figure 1A, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, each aligned set of orthologs was used to measure rates of codon substitutions and to estimate whether the whole gene, as well as any codon, are evolving under positive selection. For this, DGINN uses a combination of methods from the following selection tools: HYPHY (BUSTED and MEME), PAML (Codeml M0, M1, M2, M7, M8, and associated Bayesian Empirical Bayes (BEB) for codon-specific analyses), and bpp (M0 NS , M1 NS , M2 NS , M7 NS , M8 NS , and associated Posterior Probabilities (PP) for codon-specific analyses) (Figure 1A, Methods for details, Picard et al 2020) (Guéguen et al, 2013; Pond et al, 2005; Yang, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies have provided important insights into the diversification of HERCs, the evolutionary analyses have certain limitations: (i) the scarcity of species analyzed (only 12 species, versus 81 species with at least 10 species per order in this current study), (ii) the overrepresentation of primates compared to other mammalian species (seven primates, two to three carnivores, two artiodactyls and one perissodactyl), (iii) the integration of highly divergent species, which may bias the genetic inferences by increasing the number of false positives (37). Moreover, a recent study in primates have shown differences in HERC5 and HERC6 selective pressures (38). Therefore, how HERC5 and HERC6 genes have evolved within mammalian orders has not been fully deciphered.…”
Section: Introductionmentioning
confidence: 99%